KOMPARASI POLA TABUHAN MUSIK IRINGAN PAWAI TATUNG TIONGHOA DAN DAYAK DI KOTA SINGKAWANG - Letisia, Bernike; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is to record the accompaniment of Tatung parade of Tionghoa and Dayak tribe, especially in Cap Go Meh ceremony in Singkawang city. Descriptive reaserch method and musical approach is used in this reasearch. The data is analyzed in qualitative. The interviewees that take part in the data is Eko Ladan, Simson Mihai, Eddyhlius sean, Chie Jun Fo and some artists who take part actively in accompiment of Tatung parade. This research is hoped be the guidence to study traditional music especially accompaniment of Tatung parade of Tionghoa ad Dayak tribes in Cap Go Meh ceremony in Singkawang city. Keywords: Comparison, beating tone, accompanimant, Tatung, Tionghoa tribe, Dayak tribe, Singkawang city.Bernike Letisia, Imma Fretisari, M.Pd, Asfar Muniir, M.PdProdi Pendidikan Seni Tari dan Musik, FKIP, UNTAN PontianakEmail: Bernike_Letisia@yahoo.com